A V-LINC Analysis of the Irish South West Cyber Security Ecosystem. (2020) - (College teacher), Hobbs, John; Byrne, Eoin; Sargent, Cliodhna; Kuli, Tabona; Cork Institute of Technology., V-LINC Research Group,; Cyber Ireland,
No abstract available